Mobile Robot with Navigation Control and Communication - Mohammad Yatim, Amirah Izzati (Universiti Teknologi PETRONAS, 2016)
Mobile Robot with Navigation Control and Communication is basically about a mobile robot where a list of instructions is needed to control the locomotion of the robot. At the same time, the robot must be able to know the location of itself and measure the distance travelled. Besides, the robot will also need to detect obstacles and avoid it along its movement from one point to another autonomously. The purpose of the project is to ensure the robot will be able to do more than basic locomotion and also to do selfcorrecting orientation. The robot is designed to implement the project in the study of autonomous navigation and path planning. Other than that, various algorithm can be applied to it with the need to physically access on-board microcontroller for programming. The method that have been used in the project is V-Methodology where it started with the Testing of Unit, Testing of Subsystem and followed by the Integration of the Subsystems as the whole System. The purpose of using V-Methodology is to prevent problem that might occur in future which it can be detected earlier during the Testing of Subsystem.